A new technique for interpreting depolarization measurements using the CRL atmospheric lidar in the Canadian High Arctic - McCullough, Emily M (Scholarship@Western, 2015)
Linear depolarization measurement capabilities were added to the CANDAC Rayleigh-Mie-Raman lidar (CRL) at Eureka, Nunavut, in the Canadian High Arctic. This upgrade enables inferences of the phases (liquid versus ice) of cold and mixed-phase clouds, including during polar winter. A rotating-polarizer module was installed in the lidar, and depolarization measurements were calibrated according to existing methods. An alternate calculation technique, using the lidar's existing visible Rayleigh elastic channel in combination with the new rotating polarizer channel, was developed. A detailed mathematical description of both methods and their calibrations is presented. The new method is superior to the traditional method for the CRL: It has lower uncertainty, and gives depolarization parameter values at higher spatial-temporal resolution.